1998
DOI: 10.1523/jneurosci.18-01-00458.1998
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Presynaptic and Postsynaptic Mechanisms in a Cellular Analog of Classical Conditioning atAplysiaSensory-Motor Neuron Synapses in Isolated Cell Culture

Abstract: Temporal pairing of presynaptic activity and serotonin produces enhanced facilitation at Aplysia sensory-motor neuron synapses (pairing-specific facilitation), which may contribute to classical conditioning of the gill and siphon withdrawal reflex. This cellular analog of conditioning is thought to involve Ca2+ priming of the cAMP pathway in the sensory neurons. Consistent with that idea, we have found that pairing-specific facilitation by serotonin is greatly reduced by presynaptic injection of a slow Ca2+ ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 34 publications
9
80
0
2
Order By: Relevance
“…They randomly summate during the down state of slow oscillations and may act in concert with slow hyperpolarization-activated cation currents to depolarize cortical pyramidal cells above threshold (49). Assuming that the probability of miniature excitatory postsynaptic potentials during the silent down phase is selectively enhanced at synapses previously activated during associative learning (50)(51)(52)(53), this ongoing miniature activity could well explain the present observation of increased coherence of slow oscillations between cortical regions previously engaged in the learning process.…”
Section: Discussionmentioning
confidence: 60%
“…They randomly summate during the down state of slow oscillations and may act in concert with slow hyperpolarization-activated cation currents to depolarize cortical pyramidal cells above threshold (49). Assuming that the probability of miniature excitatory postsynaptic potentials during the silent down phase is selectively enhanced at synapses previously activated during associative learning (50)(51)(52)(53), this ongoing miniature activity could well explain the present observation of increased coherence of slow oscillations between cortical regions previously engaged in the learning process.…”
Section: Discussionmentioning
confidence: 60%
“…4 A and B) in which the reflex is mediated in part by monosynaptic excitatory postsynaptic potentials (EPSPs) from LE siphon sensory neurons to LFS siphon motor neurons in the abdominal ganglion (30). Sensitization is due in part to presynaptic facilitation of those EPSPs by PKA (43,44) and conditioning to activity-dependent facilitation of the EPSPs (28), which involves two mechanisms that interact (29): activity-dependent enhancement of the facilitation due to Ca 2+ priming of adenylyl cyclase and greater production of cAMP and activation of PKA in the sensory neurons (43)(44)(45)(46)(47)(48)(49)(50)(51), and Hebbian potentiation due to Ca 2+ influx through NMDA-like receptor channels in the motor neurons (52)(53)(54)(55).…”
Section: Hcn Channels Contribute To Behavioral Conditioning But Notmentioning
confidence: 99%
“…Long-term potentiation (LTP) (Lin & Glanzman, 1994b), as well as several associative forms of learning-related plasticity (Murphy & Glanzman, 1996;Schacher et al 1997;Bao et al 1998), of sensorimotor connections all require a rise in postsynaptic intracellular Ca 2+ . To test whether the effect of 5-HT on the Glu-PSP depends upon intracellular Ca 2+ in the motor neuron, we added BAPTA (100-200 mM) to the standard micropipette solution.…”
Section: Bapta Blocks 5-ht-induced Facilitation Of the Glutamate Respmentioning
confidence: 99%
“…This idea is supported by the discovery that the firing of identified serotonergic facilitatory neurons in Aplysia can remain significantly elevated for > 10 min after a single, brief tail shock . A possible objection to the idea that postsynaptic facilitation contributes to behavioural sensitization comes from a study by Bao et al (1998), who reported that the facilitation of sensorimotor synapses in culture induced by brief treatment with 5-HT is not affected by postsynaptic application of BAPTA. However, we have found that the facilitation of the sensorimotor synapse induced by a 10 min application of 5-HT, or by tail nerve shock, is significantly reduced when BAPTA is present in the motor neuron (Li et al 2001;Roberts & Glanzman, 2001).…”
Section: -Ht Facilitatesmentioning
confidence: 99%